Cryoballoon atrial fibrillation ablation: Single‐center safety and efficacy data using a novel cryoballoon technology compared to a historical balloon platform. (10th February 2021) - Kochi, Adriano N.; Moltrasio, Massimo; Tundo, Fabrizio; Riva, Stefania; Ascione, Ciro; Dessanai, Maria A.; Pizzamiglio, Francesca; Vettor, Giulia; Cellucci, Selene; Gasperetti, Alessio; Tondo, Claudio; Fassini, Gaetano
Abstract: Introduction: Catheter ablation is superior to drugs regarding atrial fibrillation (AF) recurrence, symptoms improvement, and mortality reduction in heart failure. POLARx™ is a novel cryoballoon, with technical improvements seeking to improve outcomes. So far, its clinical evidence is restricted to a case report. Methods: To compare the POLARx™ cryoballoon procedural safety and efficacy to the already established Arctic Front Advance PRO™ (AFAP) in a single‐center cohort study, consecutive patients undergoing AF cryoablation with the POLARx™ were enrolled. Data were prospectively gathered. POLARx™ patients were compared with a historical cohort of patients submitted to AF cryoablation with the AFAP. Results: Seventy patients were analyzed, 20 in POLARx™, and 50 in the AFAP group. They all underwent first‐time pulmonary vein isolation, 77% were male, 94% had paroxysmal AF, median age was 62.5 years, median CHA2 DS2 ‐VASc 1, left‐atrium size 34 ml/m², and 65% were receiving anticoagulation. The primary end‐point, all pulmonary veins isolation, was 100% in both groups. The complication rate was similar (0% POLARx™ vs. 5.7% AFAP, p  = .39). The median total procedural time was longer in the POLARx™ group (90 min vs. 60 min, p  < .001), but the overall time‐to‐isolation (TTI; 44.8 s vs. 39 s, p  = .253) and ablation time (15 min vs. 13.7 min, p  = .122) was similar between POLARx™ and AFAP groups, respectively. Despite equal TTI, the POLARx™ had a lower minimal temperature reached (−57°C vs −47°C, p  < .001). Conclusion: The novel POLARx™ cryoballoon had similar efficacy and safety compared with the AFAP. It was also associated with longer procedural times, similar TTI, and lower minimum temperature reached.